Problems and Poetics of Defoe's Novel Adventure of Robinson Crusoe - Narbayevna, Arazdurdiyeva Annasoltan (International Journal on Human-Computing Studies, 2023)
The topicality of the given paper is "Adventure of Robinson Crusoe" is written by Daniel Defoe who was well known English writer. An interesting aspect of the prominent literary work," Adventure of Robinson Crusoe" is the a man struggles to survive after being shipwrecked on a deserted island. According to the novel Robinson Crusoe cannot overcome his great desire to cross the seas in search of adventure. This essay will analyze the characteristics and personalities of the novel. Characters: Robinson Crusoe, Friday, Xury, Portuguese captain, the widow and others.